The Effects of Consumer Behavior and Digital Literacy on Consumption Patterns in Students - Nur Fitri; Endang Herawan; Yopi Nisa Febianti (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2022)
This research attempted to figure out: the partial effect of consumer behavior on consumption patterns among students, the partial effect of digital literacy on consumption patterns among students, and the simultaneous effect of consumer behavior and digital literacy on consumption patterns among students. It used a quantitative method, with the population of this research being students of the Faculty of Teacher Training and Education of Universitas Swadaya Gunung Jati in Academic Year 2018–2019, from which a sample of 82 respondents were extracted. Data analysis was conducted using a descriptive analysis and an inferential statistical analysis using SPSS 25. The findings showed the following: 1) Consumer behavior had a significant positive effect on consumption patterns among students, because tcount (3.224) > ttable (1.994), consumer behavior was considered to have a partial influence on consumption patterns among students. 2) Digital literacy was also found to have a significant positive effect on consumption patterns among students, because tcount (2.686) > ttable (1.994), digital literacy was considered to have a limited influence on student consumption patterns. Lastly, consumer behavior and digital literacy had a simultaneous effect on consumption patterns among students, because it was found that Fcount (10.76) > Ftable (3.09).